Promosi Kesehatan Pelaksanaan Hidup Bersih Dan Sehat Pada Lansia - Anggie Annisa Permatasari; Nannyk Widyaningrum; Dinda Cita Lolita; Chafifah Chusnul Chotimah (Compromise Journal Community Proffesional Service Journal, 2023)
Each individual must have their own awareness and play an active role in practicing PHBS (Implementation of Clean and Healthy Living) in everyday life. All health behaviors are carried out with awareness so that family or family members can help themselves in the health sector and play a role in activities in the community. The main aim of the PHBS movement is to improve the quality of health through an awareness process which is the beginning of individual contributions in living clean and healthy daily life behavior. The general benefit of PHBS is that it increases people's awareness of wanting to live a clean and healthy life. This is so that people can prevent and overcome health problems. Apart from that, by implementing PHBS the community is able to create a healthy environment and improve the quality of life. This includes the elderly group (elderly). The elderly are an age group that has experienced decline in many aspects, namely physical, psychological and social. The existence of these limitations will greatly affect the ability/independence in implementing PHBS. The lives of aging seniors need to be managed well, emphasizing the concept of active aging, maintaining independence and quality of life in the last third of life.